ANALISIS KELAYAKAN DAN SENSITIVITAS USAHA BOLU IKAN ACEH ZAHRA DI DESA BUKIT TEMPURUNG KECAMATAN KUALASIMPANG KABUPATEN ACEH TAMIANG - Adek Aemira; Adhiana; Sakral Hasby Puarada; Irshad Ahmad Reshi (LPPM Universitas Malikussaleh - Indonesia, 2025)
This research was conducted in Bukit Tempurung Village, Kualasimpang District, Aceh Tamiang Regency. The purpose of the research was to analyze the feasibility and sensitivity of the Aceh Zahra fish cake business. The data analyze method used was descriptve qualitative and quantitative analyze. The results of this study indicate that the Aceh Zahra fish cake business in Bukit Tempurung village, Kualasimpang District, Aceh Tamiang Regency is feasible to continue. This is seen the legal aspect, market and marketing aspect, technical and technological aspect, organizational management aspect, environmental impact aspect and financial aspect. From the financial aspect, it is seen from the acquisition of NPV (Rp.868.175.300), Net B/C (8,349), IRR (191%), and BEP achieved in the 3rd year, 2st month, 8th day. Meanwhile, in the sensitivity analysis, if the price of garanulated sugar ang eggs increases by 10% with the selling price of fish cake remainingthe same, the NPV obtained is (Rp.788.196.456), Net B/C (7,672), IRR (175%), and BEP achieved in the 3rd year, 4rd month, 9th day. Keywords: Business Feasibility, Cake Business, BEP, IRR, Net B/C, NPV dan Sensitivity Analysis